Paradox of Preservations: Navigating the Dichotomy between Protected and Unprotected Heritage Sites in India and Bangladesh - Bali, Nitya; Hossain, Imamur (MAJ - Malaysia Architectural Journal, 2025)
India and Bangladesh, South Asian neighbors, boast a combined total of 45 UNESCO World Heritage Sites (42 in India; 3 in Bangladesh). The abundance of heritage sites in both the countries raises a significant issue between demarcation of protected and unprotected sites, resulting in numerous unprotected sites and contrasting character of these two types of heritage sites. The paper addresses this challenge, analyzing one protected and one unprotected heritage site in the respective national capitals of India and Bangladesh, Delhi (and Delhi NCR- National Capital Region) and Dhaka. The focus is on understanding the character and performance of a heritage site managed under a formal system versus an unprotected site. The comparative study unveils key aspects such as narratives, interpretations and understanding among the stakeholders, encompassing source communities, users, heritage or non- profit organisations/experts, communities living in the vicinity of the site, etc., behavioral patterns of the users and the management and conservation status of the site. The research study approach is explorative and qualitative. This research will perform case analyses on a protected and an unprotected heritage site in both Delhi and Dhaka, sharing similar typology and located within the same geographic region. The comprehensive examination will involve observations, site investigations, and the use of semi-structured questionnaires for thorough analysis. With the objective to safeguard, conserve, and manage the rich heritage of both countries sustainably, regardless of its formal status, the authors further delve into the importance of engaging the stakeholders in this process, need of popularising the heritage sites and fostering awareness about the importance of the heritage site among them.